Council housing: Time to invest (now, more than ever), submission of evidence to the All Party Parliamentary Group for Council Housing - Dorling, D; Goulding, R; Gray, N; Hodkinson, S; Penny, J; Robbins, G; Smyth, S; Watt, P (Defend Council Housing and Homes for All, 2023)
In 2010, the Parliamentary Council Housing Group of MPs and Defend Council Housing (DCH) published “Council Housing: Time to Invest, fair funding, investment and building council housing”. It was the result of an Inquiry that took evidence from tenants, councillors and others, and combined this in a thoroughly researched analysis of existing government policy, concluding that direct investment in council housing, accountably managed and maintained, was essential to produce and maintain the genuinely affordable and secure homes we have and need. But the 2012 ‘self-financing’ regime which promised new financial resources for Council housing, has not delivered. Councils have attempted to find alternative sources of much-needed investment, looking to Special Purpose Vehicles, Joint Ventures and Local Housing Companies. These have not brought solutions to the scale of the UK’s housing crisis, which continues to deepen. A lot has changed since 2010, and the pressures on council housing have only increased. Grenfell is a deadly symptom of what has gone wrong with UK housing policy. And the false economy of current policy is illustrated by the billions of pounds councils are having to spend on temporary accommodation. We are therefore glad to help in updating research to assess the current situation and the different investment strategies offered as an alternative to direct investment. MPs will be calling for evidence, and discussing these issues, with tenants, campaigners, trade unions and councillors around the country. This paper is intended as a starting point for that discussion, outlining relevant past and current policies and assessing what we know about their effectiveness and possible consequences.